How midwives manage rapid pre‐loading of fluid in women prior to low dose epidurals: A retrospective chart review. (12th August 2018) - Lindstrom, Hannah; Kearney, Lauren; Massey, Debbie; Godsall, Guy; Hogan, Emma
Abstract: Aim: To describe contemporary routine practice regarding rapid pre‐loading of intravenous fluid management prior to epidural analgesia during labour and birth. Background: Midwives are the key health professionals providing care for women before, during and after an epidural in labour. Part of this management involves maternal hydration; however, how midwives assess and manage maternal hydration and fluid management is not well understood. Prior to the administration of a low dose epidural for pain relief a rapid intravenous pre‐loading of between 500‐1000 mls of crystalloid fluids is administered to the pregnant women. Currently, there is limited evidence available to assess if intravenous pre‐loading reduces maternal hypotension and foetal bradycardia. Anecdotal evidence suggests that wide variation in clinical practice in relation to volume of fluid administered, fluid status assessment and clinical documentation occurs. Design: A retrospective medical health record review, in a regional Australian maternity hospital. Methods: A retrospective medical health record review chart review from women who received an epidural for pain relief during labour and birth (June–September 2015). Results: Data from 293 charts were collected, including: maternal factors; blood pressure distributions; maternal fluid status; types, concentration and timing of analgesia loading doses; IV fluid loading volumes; maternal hypotension, foetal outcomes and documentation of fluid balance charts. Wide variation in clinical practice was evident with midwives administering pre‐loading fluid volumes ranging from 250‐1000 ml. Midwifery assessment, documentation and practice pertaining to hydration was inconsistent and lacking. Conclusion: Management of intravenous fluids during labour is fragmented. Although fluid balance charts are used internationally to assess maternal hydration, documentation of fluid balance status was poor. Multi‐professional collaboration between obstetrics, anaesthetics and midwifery is required to address this wide variation and reach consensus on best practice based on what evidence is currently available. Abstract : 目标: 描述在分娩过程中, 在硬膜外麻醉之前快速预压静脉液体的现代常规处理方法 背景: 助产员是为在硬膜外麻醉下的孕妇在分娩前、分娩期间和分娩后提供护理的主要卫生专业人员。这一部分涉及到母体水化;然而, 目前还不清楚助产员如何评估和管理母体水化和液体。在注射低剂量硬膜外麻醉药剂进行止痛前, 给孕妇快速静脉预压注射500‐1000 ml的晶体液。目前, 对于静脉预压能否缓解孕妇的低血压和胎儿心动过缓仍缺乏足够的证据。观察性证据表明, 在与液体管理、液体状态评估和临床过程记录相关的临床实践方面仍存在很大的差异。 设计: 在澳大利亚地区的一家妇产医院进行回顾性的医学健康记录审查。 方法: 对在分娩期间接受硬膜外麻醉的孕妇的回顾性医学健康记录进行审查(2015年6月至9月)。 结果: 收集了293张图表的数据, 包括:母体因素;血压分布;母胎液体状态;镇痛药物剂量的类型、浓度和时间;静脉注射液体装载量;产妇低血压, 胎儿情况和液体平衡图表绘制。临床实践的广泛变化是显而易见的, 助产员应预装250‐1000 ml的液体。助产术评估、过程记录和与水化有关的实践有一定出入并且有关上述内容的资料也较少。 结论: 在分娩过程中对于静脉注射液体的管理相对比较分散。尽管在国际上普遍使用液体平衡图表来评估母体水化, 但有关液体平衡状态的记录却很匮乏。产科、麻醉药和助产术之间的多专业合作需要解决这一广泛的差异, 并基于目前可用的证据, 就最佳实践达成共识。